2017
DOI: 10.1097/txd.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Intestinal Microbiota in Liver Transplantation

Abstract: BackgroundIncreasing evidence suggests that the intestinal microbiota plays an important role in liver diseases. However, the dynamics of the intestinal microbiota during liver transplantation (LT) and its potential role in clinical course remain unknown.MethodsWe prospectively analyzed the intestinal microbiota of 38 patients who underwent LT in Kyoto University Hospital. We characterized the microbial compositions of fecal specimens from LT patients using a metagenomics approach by an Illumina MiSeq platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 36 publications
1
70
0
1
Order By: Relevance
“…Concerning with the relation of gut microbiome before LT and the post-LT complication, cirrhotic patients with decreased microbial diversity before LT were more likely to develop postoperative infections than those with stable microbiota consisting of slight microbial dysbiosis [229,230]. Other clinical and experimental studies have also demonstrated that the gut microbiota disturbance, especially loss of diversity, can be associated with infection and rejection risk after LT. [226,231,232].…”
Section: Gut Microbiome Before and After Liver Transplantationmentioning
confidence: 99%
“…Concerning with the relation of gut microbiome before LT and the post-LT complication, cirrhotic patients with decreased microbial diversity before LT were more likely to develop postoperative infections than those with stable microbiota consisting of slight microbial dysbiosis [229,230]. Other clinical and experimental studies have also demonstrated that the gut microbiota disturbance, especially loss of diversity, can be associated with infection and rejection risk after LT. [226,231,232].…”
Section: Gut Microbiome Before and After Liver Transplantationmentioning
confidence: 99%
“…A number of studies have evaluated changes in the gastrointestinal microbiota as a consequence of transplantation (Table ) . We conducted searches in MEDLINE, Embase and CINAHL from database inception to May 2019.…”
Section: Gastrointestinal Microbiota and Transplantationmentioning
confidence: 99%
“…A number of studies have evaluated changes in the gastrointestinal microbiota as a consequence of transplantation (Table 1). [36][37][38][39][40][41][42][43][44][45][46] We conducted searches in MEDLINE, Embase and CINAHL from database inception to May 2019. A MEDLINE search strategy for obtaining studies evaluating changes in the gastrointestinal microbiota in transplant recipients are provided in Supplementary Table S1.…”
Section: Gastrointestinal Microbiota and Transplantationmentioning
confidence: 99%
“…To determine whether RFX treatment is an independent predictor of EAD in liver transplant patients, we conducted multivariate analysis based on a step-wise logistic regression model by screening "pre-OLT Abx-free or RFX <10 days" simultaneously with donor Abx use; recipient age, sex, and BMI; MELD score; disease etiology; concomitant HCC; cold/warm ischemia time; blood transfusions; donor age, sex, BMI, and race; DCD; donor laboratory data (AST, ALT, T-bil); Abx use during surgery; as well as post-OLT Abx and basiliximab therapy. Notably, "pre-OLT Abx-free or RFX <10 days" was identified as one of the predictive factors of EAD (OR = 2.530, 95% CI: 1.031-6.210, P = 0.043), along with donor BMI (kg/m 2 , OR = 1.077, 95% CI: 1.009-1.150, P = 0.026); liver pathophysiology has emerged as an attractive research field, recent studies have documented putative associations between intestinal microbial characteristics and liver graft status in both animals (42) and humans (43). The loss of intestinal microbiota diversity was accompanied by high Child-Pugh and MELD scores, as well as an increased incidence of rejection episodes and bloodstream infections in liver transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of intestinal microbiota diversity was accompanied by high Child-Pugh and MELD scores, as well as an increased incidence of rejection episodes and bloodstream infections in liver transplant patients. Indeed, the frequencies of Bacteroides, Enterobacteriaceae, Streptococcaceae, and Bifidobacteriaceae were increased, whereas those of Enterococcaceae, Lactobacillaceae, Clostridiaceae, Ruminococcaceae, and Peptostreptococcaceae were decreased in OLT patients experiencing acute rejection (43). On the other hand, the potential of gut microbiota modifications to affect IRI pathology and underlying mechanisms remain largely unknown (44).…”
Section: Introductionmentioning
confidence: 99%